ANALISIS KEARIFAN LOKAL DAN STRATEGI PETANI KOPI DALAM PENGELOLAAN TANAMAN KOPI RAMAH LINGKUNGAN DI DESA HUTAGURGUR KECAMATAN DOLOK SANGGUL KABUPATEN HUMBANG HASUNDUTAN SUMATERA UTARA - Anna Nesti Zebua; Eri Sayamar; Kausar Kausar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This research aims(1) Identify the local knowledge was and is still used by the people of the coffee plant in the village of environmentally friendly Hutagurgur in dolok sanggul humbang hasundutan District of North Sumatra. (2) Determine the application of local wisdom environmentally friendly coffee plantations in the village Hutagurgur in dolok sanggul humbang hasundutan District of North Sumatra. (3) To know the strategies used by the people in the cultivation of coffee in the village Hutagurgur in dolok sanggul humbang hasundutan District of North Sumatra. This research uses a method snowball sampling technique or performed in sequence by asking for information on people who have been interviewed or contacted previously, and so on. The result showed that(1) Local wisdom undertaken coffee farmers in the village hutagurgur totaling 27 local wisdom that still exist and are not maintained. 16 local wisdom that still exist today, and 11 other local wisdom is not maintained. (2) Based on the results of the Cartesian diagram there are four quadrant explaining the importance and the power level of local knowledge. In Quadrant I stated that the level of force to demonstrate the value above the average and does not have the value of the interests of local wisdom in the village hutagurgur. In Quadrant II states that the level of interest and power on average, this shows that the farmers in the village still retains activity hutagurgur local wisdom. In Quadrant III declared that force above the average of the local knowledge and interests below the average. In Quadrant IV states that the level of interest and the strength is below average. It explains that the farmers in the village hutagurgur do not believe in things mystical. (3) Internal and External Motivation of farmers to local wisdom categorized as "good enough" with a score of 3,02 and a score of 2.98 Internal motivation for External motivation. This shows that the motivation of Internal and External gave a good response from farmers on the indicators used. Key Word: local wisdom, coffea farmers, and environment